Coworking Spaces for Strengthening Academic Libraries Role (A New Trend in The Digital Age) - Kardi, Kardi; Nurhayati, Siti; Rahman, Muhammad Fawaizur (Pustakaloka, 2024)
This research aims to encourage the role of libraries as learning resource centers. The rise of coffee shops is a challenge for library service developers. The paradigm shift and the pattern of user habits in obtaining information have had an impact on the decrease in the number of library visitors. The coffee shop offers a free space with a wide selection of food and soft drinks to meet and discuss with colleagues. The problem that arises then is how libraries can answer the challenge of changing user behavior in spreading information. This article tries to explain one of the efforts to provide a user-based service. This study uses a qualitative descriptive approach to describe the strategic role of libraries in the reality of changing people's information behavior. Secondary data from the previous article were collected and then analyzed descriptively and systematically. The validity of the supporting data is sufficient if it can answer this research problem. The results of this study provide an overview of the urgency of café-style co-working in libraries. Coworking spaces can be designed to resemble coffee shops with a variety of offerings while discussing collaboratively with visitors. Of course, the space is equipped with convenient supporting devices, such as an electricity connection, internet, adequate lighting, music, air conditioning, and flexible service hours. The coworking space in the library also provides access to services for journals and e-books. The library must also be ready to help users who have difficulties using electronic services.